Entreprenörernas åsikter om Sydveds samarbetsförmåga - Bengtsson, Carl-Johan (SLU/Dept. of Forest Products, 2006)
This report is the result of a questionnaire survey done in cooperation with the company Sydved and their contractors. The investigation concerned all their ordinary contractors. The main goal with the study was to find out the contractors opinion about the current cooperation conditions with Sydved, their opinion about the future and how to improve the cooperation.